Monitoring chip fatigue in an IGBT module based on grey relational analysis. (January 2016) - Zhou, Shengqi; Zhou, Luowei; Yu, Litao; Liu, Sucheng; Luo, Quanming; Sun, Pengju; Wu, Junke
Abstract: Chip fatigue inside an insulated gate bipolar transistor (IGBT) module is a kind of incipient defect. It can be considered as an indication of the impending failure, and is utmost important for the safe operation of IGBT modules. Therefore, monitoring the chip fatigue is one of crucial measures to enhance the operating reliability of IGBT modules. This paper presents a prognostic approach for the chip fatigue based on grey relational analysis (GRA), which uses dynamic change of the gate voltage as precursor parameter. This dynamic change is caused by aging of the intrinsic parasitic elements involved in gate drive circuit, which reflect the advent of chip fatigue. Grey relational grade is employed in this proposed prognostic approach to quantify the extent of those dynamic changes by little data, and find out potential chip fatigue. Then the operator would have a chance to schedule the maintenance and replace defective IGBT modules timely to avoid wear out. So it can be seen as a prefault diagnostic method. Finally, a confirmatory experiment is also carried out, and the correctness of the proposed approach is verified.